FREQUENCY OF ABO AND RHESUS BLOOD GROUPS IN DISTRICT SWAT, PAKISTAN - Khattak, Imranud Din; Khan, Taj Muhammad; Khan, Purdil; Shah, Syed Mukhtar Ali; Khattak, Sania Tanveer; Ali, Anwar (Journal of Ayub Medical College Abbottabad, 2008)
Background: Up till now about 400 red cells antigen have been identified. The majority are inherited by Mendelian Fashion. The ABO blood group system was first to be identified and RH blood group system was the 4th one, both are most important for blood transfusion purposes. This study is conducted to determine the frequency of ABO and Rhesus (Rh) blood groups in District Swat, NWFP, Pakistan. It is a cross sectional prospective study and was conducted at Saidu Teaching Hospital district Swat, over a period of one year. (1st Jan, 2007 to 31st Dec, 2007). Methods: A total of 22897 subjects were included in this study. Patients were collected from different wards of Saidu Teaching Hospital while the donors from common population. From each subject blood was collected, ABO and Rh blood grouping were carried out by tile method using commercially prepared anti sera. The frequency of each type was calculated. Results: Out of 22897 subjects 17141 (74.86%) were male subjects and 5756 (25.14%) were female. Out of 17141 male subjects 15597 (90.99%) and out of 5756 female subjects 5040 (87.56%) were found to be Rh-positive. The frequency of Rh-negative group in male subjects were (9.01%) where as in female subjects were (12.22%). The frequency of A, B, O and AB groups in Rh-positive male subjects were 25.63%, 29.54%, 26.04% and 9.78%, amongst female subjects, it was 24.53%, 28.06%, 25.54% and 9.43% respectively. In Rh-negative male subjects the frequency of A, B, O and AB is 2.25%, 2.88%, 3.01% and 0.88%, while amongst females it is 3.54%, 4.24%, 3.74% and 0.92% respectively. Conclusion: It is concluded from this study that frequency of Rh-positive blood group is B, O, A, and AB in both gender. Where as the most common Rh-negative in male and female subjects are O, B, A, AB, and B, O, A, and AB respectively. Keywords: ABO blood group, Rh blood group, Swat, Pakistan